Indonesia Female Principal Performance Appraisal: Gender Perspective - Widyawati, Rahma; Widowati, Anik Sri; Maemunah, Mei; Istiningsih, Istiningsih; Nurnilawati, Eny; Kurnianingsih, Widyanti (UI Scholars Hub, 2022)
Research Aims: This study aimed to determine the direct influence of communication style and individual competence on female principals' empowering leadership and performance in Yogyakarta, Indonesia. Design/methodology/approach: The respondents of this study were 220 teachers from 3 accredited high schools with female principals in Yogyakarta, Indonesia. The questionnaire was analysed using structural equation modelling with AMOS to determine the relationship between variables and using Sobel Test to test leadership as a mediating variable. Research findings: The results of this study show that communication style and competence have a positive and significant effect on leadership and performance, leadership has a significant effect on performance, and leadership acts as a mediating variable. The results also indicate that gender acts as a moderating variable by strengthening the relationship between leadership and principal performance. Theoretical Contribution/Originality: The contribution of this study is to develop and examine the direct and indirect relationship between communication style, competence, gender, leadership, and performance of principals. Managerial Implication in the South East Asian Context: The results of this study can help principals design effective leadership development programs by selecting the appropriate leadership style to improve the performance of school principals. Research limitation & Implications: This research is limited by the number of respondents and the number of predictor variables of leadership and performance. This research has important implications for future research on the joint effects of contextual factors, personal characteristics, and social network attributes in the gendering leadership in the education sector.